(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
Upper Silurian, Lower and Upper Devonian conodonts are discovered for the first time from rare calcareous beds of the Serra S’llixi Group in the Pala Manna area, in connection with the nucleus of the "Sarrabus syncline" (southeastern Sardinia) where the youngest rocks of the Palaeozoic sequence of the Genn’Argiolas Unit crop out. Consequently, clastic rocks of the conformably overlying Pala Manna Formation, also affected by the main Hercynian folding fase, could be considered Famennian—Lower Carboniferous in age. It also seems reasonable that the same rocks could be compared with the more or less coeval "Culm—type" clastic sediments of the Villasalto Conglomerate, in the nearby Gerrei region.